2018
DOI: 10.3390/cancers10090336
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Neutrophil Gelatinase-Associated Lipocalin (NGAL) in Cancer: Saint or Sinner?

Abstract: Human neutrophil gelatinase-associated lipocalin (NGAL) is a glycoprotein present in a wide variety of tissues and cell types. NGAL exists as a 25 kDa monomer, a 46 kDa homodimer (the most abundant form in healthy subjects) and a 130 kDa disulfide-linked heterodimer bound to latent matrix metalloproteinase-9. Dysregulated expression of NGAL in human malignancies suggests its value as a clinical marker. A growing body of evidence is highlighting NGAL’s paradoxical (i.e., both beneficial and detrimental) effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 86 publications
2
33
0
Order By: Relevance
“…We and others previously showed that Lcn2 levels are significantly up-regulated in tissues and urine samples from patients with invasive breast cancer (25,(27)(28)(29)(30). We further confirmed that Lcn2 gene expression was significantly up-regulated in human TNBC cell lines (MDA-MB-231 and MDA-MB-436) in comparison with nonneoplastic MCF10A cells (Fig.…”
Section: Deformable Tnlgs Breach In Vitro Tumor Endothelial Barrier Vsupporting
confidence: 84%
“…We and others previously showed that Lcn2 levels are significantly up-regulated in tissues and urine samples from patients with invasive breast cancer (25,(27)(28)(29)(30). We further confirmed that Lcn2 gene expression was significantly up-regulated in human TNBC cell lines (MDA-MB-231 and MDA-MB-436) in comparison with nonneoplastic MCF10A cells (Fig.…”
Section: Deformable Tnlgs Breach In Vitro Tumor Endothelial Barrier Vsupporting
confidence: 84%
“…There is evidence that NGAL may be a marker of disease status in chronic and acute pathological conditions, especially in inflammatory, metabolic, neurological and cancer diseases (37)(38)(39). Multiple studies have explored the possible role of NGAL in various cancer models and have shown that NGAL has beneficial and harmful functions (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…Lipocalin 2 (LCN2), a member of the lipocalin subfamily, also known as neutrophil gelatinase-associated lipocalin (NGAL), is a 25 kDa secreted glycoprotein (Bauvois and Susin, 2018). NGAL also has other forms in serum; 30 kDa isoform which probably results from differential glycosylation, 46 kDa disulfide-linked homodimer and 130 kDa heterodimer which is bound to the inactive form of the matrix metalloproteinase-9 (proMMP-9) (Bouchet and Bauvois, 2014).…”
Section: Introductionmentioning
confidence: 99%